A randomized, double-blind, multicenter, phase III study on the efficacy and safety of a combination treatment involving fimasartan, amlodipine, rosuvastatin in patients with essential hypertension and dyslipidemia who fail to respond adequately to fimasartan monotherapy - Eun-Seok Jeon; Sang Wook Lim; Seok-Yeon Kim; Hyoung-Mo Yang; Moo Hyun Kim; Moo-Yong Rhee; Seung Hwan Han; Jinho Shin; Kwang-il Kim; Jin-Ok Jeong; Ki Chul Sung; Geu Ru Hong; et al. (BMC, 2022)
Abstract Background To assess the efficacy and safety of a combination therapy involving fimasartan, amlodipine, and rosuvastatin in patients with essential hypertension and dyslipidemia who fail to respond to fimasartan monotherapy. Methods This phase III, randomized, double-blind, multicenter study was conducted in adults aged 19-70 years. Patients who voluntarily consented were screened for eligibility to enroll in the study. Patients who failed to respond to 4 weeks of fimasartan monotherapy were randomized with a 1:1:1 ratio to the fimasartan 60 mg/amlodipine 10 mg + rosuvastatin 20 mg (FMS/ALD + RSV) as study group, fimasartan 60 mg/amlodipine 10 mg (FMS/ALD) as control 1 group, and fimasartan 60 mg + rosuvastatin 20 mg (FMS + RSV) as control 2 group. The primary efficacy endpoints were the change in the sitting systolic blood pressure and the rate of change in the low-density lipoprotein cholesterol (LDL-C) level from baseline to 8 weeks. The adverse events, adverse drug reactions, physical examination findings, laboratory test results, electrocardiograms, and vital signs were evaluated to assess safety in the study. Results Of 138 randomized patients, 131 were conducted efficacy analysis, and 125 completed the study. For the change in LDL-C and sitting SBP (SiSBP) as primary efficacy assessments, the change in LDL-C at week 8 was significantly reduce in the FMS/ALD + RSV group than in the control 1 group (P < 0.001). The change in SiSBP at week 8 were greater reduce in the FMS/ALD + RSV group than in the FMS + RSV group (both P < 0.001). For the safety evaluation, there were no differences among the treatment groups in the incidence of adverse drug reactions. Conclusions The fimasartan/amlodipine + rosuvastatin combination therapy can effectively and safely lower blood pressure and improve lipid levels in patients with essential hypertension and dyslipidemia who fail to respond adequately to fimasartan monotherapy. Trial registration NCT03156842, Registered 17 May 2017